Blue-Blood Pig Thorax Model Increases Residents' Confidence in Internal Mammary Dissection - Gunderson, Kirsten A.; Zeng, Weifeng; Nkana, Zeeda H.; Matabele Wood, Kasey Leigh; Lyon, Sarah M.; Albano, Nicholas J.; Poore, Samuel O. (Journal of Reconstructive Microsurgery, 2023)
Background Preparation of the recipient vessels is a crucial step in autologous breast reconstruction, with limited opportunity for resident training intraoperatively. The Blue-Blood–infused porcine chest wall—a cadaveric pig thorax embedded in a mannequin shell, connected to a saline perfusion system—is a novel, cost-effective ($55) simulator of internal mammary artery (IMA) dissection and anastomosis intended to improve resident's comfort, safety, and expertise with all steps of this procedure. The purpose of this study was to assess the effect of the use of this chest wall model on resident's confidence in performing dissection and anastomosis of the IMA, as well as obtain resident's and faculty's perspectives on model realism and utility.Methods Plastic surgery residents and microsurgery faculty at the University of Wisconsin were invited to participate. One expert microsurgeon led individual training sessions and performed as the microsurgical assistant. Participants anonymously completed surveys prior to and immediately following their training session to assess their change in confidence performing the procedure, as well as their perception of model realism and utility as a formal microsurgical training tool on a five-point scale.Results Every participant saw improvement in confidence after their training session in a minimum of one of seven key procedural steps identified. Of participants who had experience with this procedure in humans, the majority rated model anatomy and performance of key procedural steps as “very” or “extremely” realistic as compared with humans. 100% of participants believed practice with this model would improve residents' ability to perform this operation in the operating room and 100% of participants would recommend this model be incorporated into the microsurgical training curriculum.Conclusion The Blue-Blood porcine chest wall simulator increases trainee confidence in performing key steps of IMA dissection and anastomosis and is perceived as valuable to residents and faculty alike.
Keywords: microsurgery; surgical simulation; surgical education; autologous reconstruction